2021
DOI: 10.35723/ajie.v4i2.144
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Boarding School-Based Madrasah: Policy Efforts to Reform the Superior Education Model

Abstract: Madrasah is an alternative educational institution and has the same opportunity to become an educational institution taken into account in social change dynamics. However, as a logical consequence, madrasas must develop each sector to achieve its organizational goals. This study examines the opportunities and challenges of developing madrasas, particularly those based on an Islamic boarding school. This study is a literature study, so that the method of analyzing data is by reviewing and collecting information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Independently develop real-world communities or campuses around a theme and assess distinctive characters. The findings revealed that: (1) Islamic Education teachers were prepared for the independent learning policy, but were less prepared to implement AKM and character surveys as a replacement for the National Examination in terms of cognitive aspects, physical readiness, and psychological readiness; and (2) State Madrasah Tasanawiyah 9 Madiun's learning support facilities were in better condition than average for receiving the independent learning policy [34].…”
Section: Pgri 6 Palembang Junior High Schoolmentioning
confidence: 99%
“…Independently develop real-world communities or campuses around a theme and assess distinctive characters. The findings revealed that: (1) Islamic Education teachers were prepared for the independent learning policy, but were less prepared to implement AKM and character surveys as a replacement for the National Examination in terms of cognitive aspects, physical readiness, and psychological readiness; and (2) State Madrasah Tasanawiyah 9 Madiun's learning support facilities were in better condition than average for receiving the independent learning policy [34].…”
Section: Pgri 6 Palembang Junior High Schoolmentioning
confidence: 99%
“…In carrying out its activities, this school is under the auspices of the Ministry of Education and Culture and the Ministry of Religion. Independent, Skilled and Loves the Qur'an An Islamic educational institution that combines academic learning, character building and comprehensive teaching of the Qur'an Discipline of worship and habituation of noble character (5 daily congregational fardhu prayers, qiyamullail and sunnah prayers, sunnah fasting) Interaction with the Koran intensively 3x a day including tahsin, tahfizh and tafhim programs with a target of 4-6 Juz per year Intensive Arabic & English language (cultum in Arabic and English ), three-language muhadhoroh, muhadatsah and vocabulary enrichment, drama performances in Arabic & English and rihlah lughawiyah to Pare Kediri (Afista & Abu Bakar, 2020). Takwin Syakhsiyah activities include morning and evening coaching, weekly coaching, and independent camping.…”
Section: Description Of the Research Locationmentioning
confidence: 99%
“…To create quality education, all education components should be of a high standard, such as the curriculum of the madrasa [24]. This is ideally and independently designed as a guide or reference in creating a quality educational process, according to the vision and mission of the madrasa [25]. The notion was also comprehended as a general description (miniature) of an educational process, based on having good quality learning outcomes that were unable to be obtained without the presence of a curriculum [26].…”
Section: The Curriculummentioning
confidence: 99%